2022
DOI: 10.7759/cureus.29468
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Disadvantages of Using St. John's Wort as a Treatment for Depression

Abstract: Background and objectives: St. John's wort (SJW) extracts are currently being used to treat depression of various degrees of severity. While many studies have shown it to be superior to placebo, data regarding the effectiveness of using SJW as a stand-alone treatment compared with standard antidepressants has yet to be proven conclusively. This study aims to understand the advantages and disadvantages of SJW as a treatment modality for depression.Methods: The authors searched PubMed, JAMA network, Springer Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…One study compared SJW with conventional antidepressants, including SSRIs and TCAs. The common adverse effects of SJW were comparable to those of conventional antidepressants, with the added benefits of low cost and minimal withdrawal symptom rates [63]. Although categorized solely as a dietary supplement by the Food and Drug Administration (FDA) and not classified as a drug [63], it is important to mention that while SJW has not obtained FDA approval owing to safety concerns, FDA-approved drugs with similar actions and side-effect profiles as SJW have been available for a long time [64].…”
Section: Adverse Events Of Sjw and Precautionsmentioning
confidence: 88%
“…One study compared SJW with conventional antidepressants, including SSRIs and TCAs. The common adverse effects of SJW were comparable to those of conventional antidepressants, with the added benefits of low cost and minimal withdrawal symptom rates [63]. Although categorized solely as a dietary supplement by the Food and Drug Administration (FDA) and not classified as a drug [63], it is important to mention that while SJW has not obtained FDA approval owing to safety concerns, FDA-approved drugs with similar actions and side-effect profiles as SJW have been available for a long time [64].…”
Section: Adverse Events Of Sjw and Precautionsmentioning
confidence: 88%
“…For instance, foods, including fruits, alcohol, teas, and herbs are commonly known to induce or inhibit the activity of drug metabolising enzymes, such as CYPs ( Fujita, 2004 ). For example, St John’s wort ( Hypericum perforatum ) extract has long been associated with relieving the symptoms of mild depression, demonstrating a high safety and efficacy profile ( Canenguez Benitez et al, 2022 ). However, research has shown that St John’s wort is a potent inducer of CYP enzyme CYP3A4, resulting in the enhanced metabolism and decreased blood concentration of drugs metabolised by this enzyme, including common antidepressants citalopram, fluoxetine, and sertraline ( Zhou et al, 2004 ).…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…20 . H. perforatum has been shown to elevate the level of different monoamines and 5HT in the cerebellum, amygdala, hippocampus, and prefrontal cortex by inhibiting monoamine neurotransmitters like a substance called (5-HT), noradrenaline, and dopamine levels 21 . One of the main purposes of H. perforatum is overexpression of the 5-HT receptors, which has the effect of upregulating the neurons, it in turn results in a dopamine-related component lowering the neurons' background activity.…”
Section: Herbal Plants With Anxiolytics and Antidepressants Activitymentioning
confidence: 99%